The right to legal aid in civil litigation in Poland and in Spain. Is it the state's task relating to justice or administration? - Joanna Misztal-Konecka (Journal of Modern Science, 2019)
Objectives The article presents the right to legal aid in civil litigation in Poland and in Spain.